Aplikasi Konsultasi Pelayanan Pengobatan Gangguan Mental Anak Berbasis Website (Studi Kasus: Apotek Segar Sehat Jakarta) - Aji Sofian; Imam Sutanto (Publikasi Indonesia, 2023)
Consultation scheduling is a form of activity in determining the order of treatment in health services which is marked by the name, type of service and schedule of a patient who wants to take treatment. Apotek Segar Sehat is a pharmaceutical service that provides psychiatric and physiotherapy practitioner services during the child's growth and development. In the mechanism of the treatment business process, everything is based on a predetermined schedule. However, there are problems in the schedule making process, namely, treatment scheduling is done manually with prospective patients first needing to register and determine the schedule via telephone. This will be less efficient because users via telephone sometimes like full or busy calls, plus admin staff need to record these patients one by one. This makes the administrative process work less effective. Based on these problems, the idea arose to make Treatment Consultation Application in Children's Mental Disorders. Where this prototype was built for prospective patients in making a consultation schedule through the Webiste page. The Waterfall Paradigm is used as a software development method based on data obtained by conducting interviews with pharmacies and literature studies. Thus the expected results from this research can be used as a solution to overcome problems in the Consultation Scheduling process.